2020
DOI: 10.1186/s12991-020-00277-4
|View full text |Cite
|
Sign up to set email alerts
|

Discerning undifferentiated anxiety from syndromal anxiety in acute-phase schizophrenia

Abstract: Background: Literature on anxiety in schizophrenia is confined to well-established diagnostic syndromes and the diagnostic category of unspecified anxiety disorder has not been quantitatively verified in this population. This study examined whether anxiety that is not differentiated into the well-established syndromes is empirically discernible from syndromal anxiety and no anxiety in acute-phase schizophrenia. Methods:After sampling 111 acute-phase schizophrenia patients, they were stratified into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Anxiety in schizophrenia is common and may present concurrently both as a specified anxiety disorder and in an undifferentiated way [1]. The pooled prevalence rate of specified anxiety disorders in schizophrenia was 38.3% in a meta-analysis of 52 studies, which was higher than the 28.8% reported for the general population [2,3].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Anxiety in schizophrenia is common and may present concurrently both as a specified anxiety disorder and in an undifferentiated way [1]. The pooled prevalence rate of specified anxiety disorders in schizophrenia was 38.3% in a meta-analysis of 52 studies, which was higher than the 28.8% reported for the general population [2,3].…”
Section: Introductionmentioning
confidence: 84%
“…Undifferentiated anxiety may be understood as a constellation of clinically significant anxiety features that do not meet diagnostic criteria for any of the specified anxiety syndromes, for which the DSM-IV and DSM-5 respectively provide an anxiety disorder not otherwise specified and an unspecified anxiety disorder [5,6]. Undifferentiated anxiety may also be understood as an anxiety feature that is not specific to any one specified anxiety disorder [1]. Palpitations, hypervigilance, restlessness, trembling, and feelings of tension are examples.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is one of the prominent features observed among patients with schizophrenia. It often precedes and accompanies schizophrenia and is one of its risk factors (1)(2)(3)(4)(5). A metaanalysis of 52 studies showed that the prevalence rate of anxiety and related disorders in schizophrenia is 38.3% (2), and a recent study reported it to be higher, 45% (4).…”
Section: Introductionmentioning
confidence: 99%
“…After pooled analysis, the data demonstrated a better psychometric property. They approved its validity and reliability for measuring the specified and undifferentiated anxiety in schizophrenia patients, providing an accurate measurement of anxiolytic treatment effects ( 1 ). Considering this as a reference, we tried to introduce S-SARS use in Chinese patients to protect the prognostic of the patients better.…”
Section: Introductionmentioning
confidence: 99%
“…16 In parallel, individuals with schizophrenia, especially those presenting in the acute phase, should be checked for unspecified anxiety disorder. 17 The results of relevant studies indicate that individuals with schizophrenia benefit from targeted interventions for anxiety disorder. 18 Previously, the diagnosis of separation anxiety disorder was limited to childhood and adolescence; however, the extension of timing for the onset of symptoms into adulthood, prolongation of the duration of symptoms to a minimum of six months, and modification of attachment figures to include children, spouse, and significant others has resulted in the categorization of adult separation anxiety disorder as a separate disorder in the Diagnostic and Statistical Manual of Mental Disorders, version 5 (DSM-5).…”
Section: Introductionmentioning
confidence: 99%